On Frankincense - Maksimović, Zoran (Archives of Pharmacy, 2021)
Boswellia species (Burseraceae) are trees or shrubs whose area of distribution covers the wide geographic area between North Africa and India. After incision, their bark produces oleo-gum resin known as frankincense (Olibanum). In traditional medicine, frankincense is often used for medical treatment of arthritis, asthma, ulcerative colitis, coughs, sores, and wound healing. Various frankincense preparations are marketed almost exclusively as dietary supplements. Indian frankincense, or Olibanum indicum, is official in the European Pharmacopoeia. The major components of frankincense are boswellic acids, among which the most important and abundant is 3-O-acetyl-11-keto-β-boswellic acid (AKBA). AKBA is a 5-lipoxygenase inhibitor with anti-inflammatory and anti-arthritic effects. Besides, frankincense contains essential oil, whose composition greatly depends on the biological source, as well as arabinogalactans and glycoproteins. In small clinical trials, certain benefits of various frankincense preparations have been demonstrated in cases of ulcerative colitis, bronchial asthma, mild symptoms of irritable bowel syndrome, and various disorders of osteo-muscular system. However, for collagenous colitis and Crohn’s disease remission maintenance, the evidence is ambiguous or negative. AKBA-containing extract was found advantageous in patients with osteoarthritis, and to some extent with rheumatoid arthritis. Almost all the trials had serious flaws in experimental design, such as insufficient sample size and/or incomplete reporting of data. For any clinical recommendation of frankincense preparations, larger and better-designed studies are needed.